A Modified Maximal Divergence Sequential Auto-Encoder and Time Delay Neural Network Models for Vulnerable Binary Codes Detection - Albahar, Marwan Ali (IEEE access, 2020)
Since the risks associated with software vulnerabilities are rapidly increasing, the detection of vulnerabilities in binary code has become an important area of concern for the software community. However, research studies associated with the detection of vulnerabilities in binary code remain limited to the handcrafted features referenced by a specific group of experts in the field. This paper considers other possibilities to add on the subject of detecting vulnerabilities in binary code. Herein, we utilize recent studies conducted on the topic of deep learning and specifically study a maximal divergence sequential auto-encoder (MDSAE) model to propose a modified version (MDSAE-NR). We also propose an altered interpretation of time-delay neural network (TDNN-NR) by incorporating a new regularization technique that produced optimized results. Finally, both models achieved good predictive performance using different evaluation metrics such as accuracy, recall, precision and F1 score compared to the baseline results. Based on the results of our experiments, we observed a 2 to 2.5% average improvement in each performance measure of interest.